Spatio-temporal dynamics and biogeochemical properties of green seawater discolorations caused by the marine dinoflagellate Lepidodinium chlorophorum along southern Brittany coast. (30th September 2022) - Roux, Pauline; Siano, Raffaele; Souchu, Philippe; Collin, Karine; Schmitt, Anne; Manach, Soazig; Retho, Michael; Pierre-Duplessix, Olivier; Marchand, Laetitia; Colliec-Jouault, Sylvia; Pochic, Victor; Zoffoli, Maria Laura; et al.
Abstract: Blooms of the marine dinoflagellate Lepidodinium chlorophorum cause green seawater discolorations affecting the recreational use and the tourism economy along southern Brittany (NE-Atlantic, France). Hypoxic conditions associated with phytoplankton biomass recycling are suspected to cause fauna mortalities. An in situ monitoring was performed in 2019 to characterise the seasonal variability of L. chlorophorum . This species was observed from May to November, with a maximum abundance in June–July. Specific bloom sampling demonstrated a dominance of L. chlorophorum within microphytoplankton, and documented its vertical distribution. Satellite observation was used to compute the surface extent of the bloom and to highlight the importance of small-scale temporal variability, with tidal currents being a primary driver of surface distribution of the bloom. Stratification contributed to promoting the bloom of L . chlorophorum . High concentrations of phosphate and ammonium, together with transparent exopolymer particles (TEP), were recorded within the bloom. Bacterial stimulation, leading to nutrient remineralisation or mucus facilitating mixotrophy, is suggested to sustain bloom development. Hence, TEP production might provide an ecological advantage for the dinoflagellate, conversely causing negative effects on the environment and biological resources through hypoxia. These first insights constitute a baseline for further studies in other ecosystems impacted by this species. Highlights: Lepidodinium chlorophorum occurred from May to November in southern Brittany. Water column stratification could favour L. chlorophorum blooms. High-resolution (5 days, 20 m) satellite observation made possible to document the bloom surface extent and to highlight the influence of tides on the spatial distribution of L. chlorophorum. High transparent exopolymer particles (TEP) concentrations are measured inside a bloom. Bacterial remineralisation might sustain bloom development and cause hypoxia, likely contributing to bivalve mortality.